Effects of photoperiod on some reproductive organs and endocrine glands of young rams : a thesis presented in partial fulfilment of the requirements for the degree of Master of Agricultural Science at Massey University - Zweng, Martin John (Massey University, 1968)
Following Marshall's (1937) observation that ewes transported from one hemisphere to another reversed their oestrous and anoestrous seasons to conform to a new seasonal environment, it was hypothesized that daylength (photoperiod) had some effect on the reproductive activity of the ewe. Sykes and Cole (1944) exposed ewes to an experimental decrease in daylength of 6 hours over a period of 5 weeks. The experiment commenced in the Spring when daylength was 11.5 hours. Breeding occurred earlier that normal and lambs were produced four to five months before the usual time. Criticism of this work arose because of the use of only a limited number of animals, and the fact that the animals were of Ramboiillet stock, a breed known to show oestrous activity, under natural conditions, in the Spring and early Summer. These preliminary observations seemed to indicate that the ewe exhibited sexual activity in response to a "short" or "shortening" daylength. From these initial experiments, other observations of natural breeding seasons and more sophisticated photoperiod experiments have followed.
Keywords: Rams; Effect of light on; Reproduction